Discrepancies between bone marrow histopathology and clinical phenotype in BCR-ABL1-negative myeloproliferative neoplasms associated with splanchnic vein thrombosis. Issue 5 (May 2015) - Gianelli, Umberto; Iurlo, Alessandra; Cattaneo, Daniele; Bossi, Anna; Cortinovis, Ivan; Augello, Claudia; Moro, Alessia; Savi, Federica; Castelli, Roberto; Brambilla, Cecilia; Bianchi, Paola; Primignani, Massimo; et al.
Highlights Splanchnic vein thrombosis is associated to MPNs in about half of cases. Search for JAK2 V617F in SVT patients is not always enough for the diagnosis of MPN. Bone marrow histology should represent a key component in SVT. Bone marrow histology is not enough to distinguish among PV, PMF or ET. An approach considering morphological, clinical and molecular data is needed.